Capital Market Reaction to The Replacement of the Minister of Finance in 2025 - Mia Helmalia Putri; Agus Satrya Wibowo; Theresia Mentari; Verra Rizki Amelia (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The change in Indonesia’s Minister of Finance on September 8, 2025, from Sri Mulyani to Purbaya became a political event that caught the attention of the capital market. This study aims to determine whether this event contains significant information that influences investor behavior, particularly through abnormal returns and trading volume activity of LQ45 stocks. The observation period spanned 30 days before and after the ministerial change, totaling a 61-day window. The analysis results indicate no significant differences in abnormal returns or trading volume activity during this period. Although the LQ45 index briefly declined on the day of the inauguration, the market reaction proved to be temporary and quickly adjusted. These findings confirm that economic fundamentals have a dominant influence over short-term political sentiment in shaping investor decisions in the Indonesian capital market.